ANALISIS PENGARUH KEMAMPUAN (ABILITY) DALAM MENINGKATKAN KINERJA PEGAWAI PADA SEKSI KELEMBAGAAN SARANA DAN PRASARANA PKLK DINAS PENDIDIKAN PROVINSI JAMBI - Ratih Elvirawati; KA Rahman; Mohamad Muspawi (Universitas Muhammadiyah Sorong, 2022)
This research aims to knowing the Influence of Abilities (Ability) in improving Performance Employees in the Institutional Section of Facilities and PKLK infrastructure of the Jambi Provincial Education Office. This study used Descriptive Statistical Analysis Techniques and Regression Analysis Techniques as a Data Analysis Method and Test the Hypothesis. The results of descriptive statistical calculations found that the employees had carried out the Performance well, have the ability which is good. Almost all indicators of the variables studied have met the requirements of reliability and valid. The results showed that Ability work contributes 73.4% to Performance employees in the Facilities Institutional Section and PKLK infrastructure of the Jambi Provincial Education Office. Ability employees who need to enhanced is an ability employees for doing difficult work as well as ability think to doing various kinds of work, through the participation of employees in various existing training activities. To Performance Employees that need to be addressed are those related to the employee's willingness to work beyond the target. Kata kunci: Kemampuan, Kerja, Kinerja.